PENGARUH KEMAMPUAN KONEKSI DAN DISPOSISI MATEMATIS TERHADAP HASIL BELAJAR SISWA SMA NEGERI 2 BALIKPAPAN - Nadhifah, Darin; Susilo, Ganjar; Permatasari, Besse Intan (Institut Agama Islam Negeri Curup, 2019)
The purpose of this research was would know if there are effect mathematics connection ability and disposition to mathematics achievement student class XI SMA Negeri 2 Balikpapan in the Academic Year of 2017/2018. The research used in this study is quantitative and the type of ex-post facto research. The research sampling technique uses cluster random sampling. Data collection techniques used in this study were in the form of tests and questionnaires. Data analysis techniques using multiple linear regression analysis with hypothesis testing using f-test and t-test as a partial test to determine the independent variable mathematical connection (X1) on learning outcomes (Y) and mathematical disposition independent variable (X2) on mathematics learning outcomes (Y) , but before testing the hypothesis it is necessary to test the classical assumptions of normality test, linearity test, independent test, multicollinearity test, and heteroscedasticity test. The results in this study are 1) there is an influence of mathematical connection ability and mathematical disposition on mathematics learning outcomes; 2) there is an influence of mathematical connection ability on mathematics learning outcomes; 3) there is an influence of mathematical disposition on the learning outcomes of mathematics.